A Randomized Controlled Trial of Plastic Drape for Prevention of Hypothermia during Umbilical Catheterization - Nuntnarumit, Pracha; Swatesutipun, Buranee; Udomsubpayakul, Umaporn; Thanacharoenpipat, Pornjit (American Journal of Perinatology, 2013)
Objective To determine the efficacy of polyethylene plastic draping in preventing hypothermia during umbilical catheterization.Methods A randomized controlled trial was conducted in newborns who required umbilical catheterization. A sterile polyethylene plastic sheet covering the procedural field was used in the plastic group, and a sterile conventional cotton drape was used in the control group.Results Sixty infants were enrolled and randomly assigned to the plastic group (n = 30) and control group (n = 30). There were no significant differences in the baseline demographic data. The use of plastic drapes was associated with a higher rectal temperature compared with the control group. Incidence of hypothermia at the end of procedure were 20% and 50% in the plastic group and control group, respectively (p = 0.03).Conclusion Polyethylene plastic draping was superior to conventional cloth draping in maintaining rectal temperature and preventing hypothermia during umbilical catheterization.
Keywords: hypothermia; prevention; umbilical catheterization; neonates